Evaluating the support and associated strain distribution in unilateral obturator with different designs: An experimental and finite element study - Mohammed Mousa; Adam Husein; Mohamed El-Anwar; Norwahida Yusoff; Hussein Alhelay; Badi Alazhari; Fadhel Alsharari; Bader AlZarea; Mohammed Sghaireen; Johari Yap Abdullah (PLoS ONE, 2025)
This study aimed to evaluate support (the resistance to tissue-ward movement) and strain distribution in unilateral obturators with four designs using Digital Image Correlation (DIC) and Finite Element Analysis (FEA). Twelve epoxy-resin models were prepared to receive removable obturators that have four designs, including acrylic resin-based obturators (ARO), linear (LDO), tripodal (TDO), and a newly modified one termed fully tripodal design obturator (FTDO) were used for DIC. The models were installed in a DIC set to receive a vertical load of 150N. The strain on the dentate and defect sides was evaluated using DIC software. Mathematically, four finite element models were prepared to receive vertical and lateral loads of 100N on two points. The support and strain were assessed using the ANSYS workbench. Using DIC, the ARO demonstrated the highest strain values on the defect area and as an entire prosthesis, followed by the LDO on the defect side. Using FEA, the TDO produced the highest strain value with anterior (oblique) and posterior loads. LDO produced the lowest support and highest strain on the anterior teeth compared to TDO and FTDO. ARO resulted in the highest total strain, while the TDO produced the lowest. Both TDO and FTDO were comparable in terms of strains and support.